Escherichia coli used as a biomarker of antimicrobial resistance in pig farms of Southern Brazil - Brisola, Maiara Cristiane; Crecencio, Regiane Boaretto; Bitner, Dinael Simão; Frigo, Angélica; Rampazzo, Luana; Stefani, Lenita Moura; Faria, Gláucia Amorim [UNESP] (Elsevier, 2019)
The objective of this study was to verify the presence of antimicrobial resistant strains of Escherichia coli in pig farms and to use it as a biomarker to evaluate phenotypic and genotypic profiles of antimicrobial susceptibility, as well as the presence of Extended Spectrum Beta-lactamases (ESBLs) and fluoroquinolone resistance genes. Several samples (n = 306) collected from swine farms (n = 100) of Southern Brazil were used for E. coli isolation: 103 of swine feces, 105 of water, and 98 of soil. E. coli isolates were submitted to the disk-diffusion test to verify their antimicrobial susceptibility, to disk-approximation test to detect ESBL-producers, and to PCR analysis to search for ESBLs genes (blaCTY-M2, blaSHV-1, blaTEM-1, blaCTX-M2, blaOXA-1, blaPSE-1) and quinolone resistance genes (qnrA, qnrB and qnrS). The percentage of E. coli isolates found in feces, water and soil samples was 66.02%, 30.48% and 35.71%, respectively. The highest percentages of resistance were obtained for sulfamethoxazole associated with trimethoprim (63.70%), colistin (45.19%) and enrofloxacin (39.26%). Regarding the levels of multidrug resistance, 37.04% of the isolates were resistant to three or more classes of antimicrobials. The most common profile (16%) of multirresistance was GEM-SUT-ENO-COL. The index of multiple resistance to antimicrobials (IRMA) was above 0.2 in 78% of the multiresistant isolates. Out of 135 E. coli isolates, 7.41% was ESBL-producers, of which 50% showed the blaCMY-M2 gene, 40% the blaTEM-1 and 70% the qnrS gene. Of non-ESBL-producing strains resistant to enrofloxacin, 13.04% were positives for qnrS gene. These results demonstrated the presence of fecal contamination in the environment, in addition to high resistance indexes for several antimicrobials, including beta-lactams and fluoroquinolones, which was confirmed by the genetic detection of ESBLs and qnr genes.
Keywords: ESBLs; Escherichia coli; Fecal contamination; Fluoroquinolones; Resistance